Adverse events in cardiovascular-related training programs in people with spinal cord injury: A systematic review. (November 2014) - Warms, Catherine A.; Backus, Deborah; Rajan, Suparna; Bombardier, Charles H.; Schomer, Katherine G.; Burns, Stephen P.
Abstract : Context: There are anecdotal reports of adverse events (AEs) associated with exercise in people with spinal cord injury (SCI) and consequent concern by people with SCI and their providers about potential risks of exercise. Enumeration of specific events has never been performed and the extent of risk of exercise to people with SCI is not understood. Objective: To systematically review published evidence to identify and enumerate reports of adverse events or AEs associated with training in persons with SCI. Methods: Review was limited to peer-reviewed studies published in English from 1970 to 2011: (1) in adults with SCI, (2) evaluating training protocols consisting of repeated sessions over at least 4 weeks to maintain or improve cardiovascular health, (3) including volitional exercise modalities and functional electrical stimulation (FES)-enhanced exercise modalities, and (4) including a specific statement about AEs. Trained reviewers initially identified a total of 145 studies. After further screening, 38 studies were included in the review. Quality of evidence was evaluated using established procedures. Results: There were no serious AEs reported. There were no common AEs reported across most types of interventions, except for musculoskeletal AEs related to FES walking. There were few AEs in volitional exercise studies. Conclusion: There is no evidence to suggest that cardiovascular exercise done according to guidelines and established safety precautions is harmful. To improve the strength of these conclusions, future publications should include definition of AEs, information about pre-intervention screening, and statements of the nature and extent of AEs.